The critical BMI hypothesis for puberty initiation and the gender prevalence difference: Evidence from an epidemiological survey in Beijing, China - Liu, Meijuan; Cao, Bingyan; Luo, Qipeng; Wang, Qiao; Liu, Min; Liang, Xuejun; Wu, Di; Li, Wenjing; Su, Chang; Chen, Jiajia; Gong, Chunxiu (Frontiers in Endocrinology, 2022)
Background: Although previous studies suggested that there is a certain level of body fat mass before puberty can be initiated, most studies have focused on girls. Objective: To investigate the relationship between precocious puberty and physical growth in school-aged children in Beijing, China. Methods: 7590 Chinese children (3591 girls and 3999 boys) aged 6–11 years were recruited in Beijing, China. Body mass index (BMI) categories were defined by WHO Child Growth Standards and central obesity were defined by sex-specific waist-to-height ratio cut-offs (≥0.46 for girls, ≥0.48 for boys). Sexual development was assessed using Tanner criteria. Results: The prevalence of general obesity and central obesity among boys was higher than that in girls. Girls had a significantly higher precocious puberty rate than boys (5.93% vs. 0.87%), particularly in those aged 7 years old (9.20%). Children in the general obesity and central obesity groups have a higher prevalence of precocious puberty and earlier median ages for the attainment of Tanner B2/T2. For girls with Tanner stages≥II at 6-year-old and 7-year-old, the mean BMI was equivalent to the 50th centile of a normal 9.9-year-old and 11.9-year-old girl, respectively. The mean BMI of boys with Tanner stages≥II at 7-year-old and 8-year-old was correspondent to the 50th centile of a normal 14-year-old and 15.3-year-old boy, respectively. For girls, general obesity appears to contribute to the risk of the development of precocious puberty to a greater extent than central obesity does. For boys, central obesity, but not general obesity, was an independent risk factor for precocious puberty. Conclusions: The prevalence of childhood obesity and precocious puberty was high in China. Precocious puberty was correlated with a large BMI. Boys had a higher threshold of BMI for puberty development than girls. Children with precocious puberty, particularly those with central obesity, should be aware of adverse cardiovascular events